The ingenious study on the formulation of thermal stability bio-based grease - Muhammad Auni, Hairunnaja; Mohd Aizudin, Abd Aziz; Mohd Azmir, Arifin; Nur Amira Fatihah, Bashari; Navinash, Nedumaran; Mohd Faizal, Ali; Muhammad Ammar, Nik Mu’tasim; Farhanah Florence, Abdullah; Muhammad Akmal, Houd (Penerbit Universiti Teknologi Malaysia, 2025)
Concerns about the dwindling supply of mineral oil, which is heavily used in products like grease, have prompted the exploration of Waste Cooking Oil (WCO) as a viable alternative. WCO, derived from improperly disposed vegetable oil, is the focus of this study, which aims to produce grease using Fumed Silica (F.S.) as a thickener. The process involves heating and filtering WCO to reduce moisture content and remove impurities, followed by formulation with additives using a homogenizer at 5000 rpm for three hours, and then cooling for a week. The resulting greases are tested for consistency, oil bleeding, separation, dropping point, and corrosion rate. All lubricants exhibit NLGI values between 00 and 4, oil bleeding from -15% to 15%, oil separation below 4%, a dropping point exceeding 350℃, and a slightly tarnished appearance against copper strips for corrosion classification. An exception is made for F.G94 due to its abnormal grease structure. Despite this anomaly, F.G90 emerges as the top-performing grease, meeting all specifications. This study highlights the effectiveness of WCO as a base oil for grease production.